Biofilm formation of Campylobacter strains isolated from raw chickens and its reduction with DNase I treatment. (January 2017) - Kim, Se-Hun; Park, Changwon; Lee, Eun-Jung; Bang, Woo-Suk; Kim, Yun-Ji; Kim, Joo-Sung
Abstract: Campylobacter is a well-known bacterial agent that causes foodborne gastroenteritis. Its biofilm-forming ability is known to be important for its survival in harsh conditions. Poultry is a main reservoir of Campylobacter . In this study, we evaluated the biofilm-forming ability, motility, and antibiotic susceptibility of Campylobacter strains isolated from commercially purchased chickens of various sources in South Korea. From 37 (30%) out of 124 chickens, a total of 78 Campylobacter isolates were obtained, and the ability of these strains to form biofilms was studied on polystyrene surfaces. We identified seven biofilm-forming strains of Campylobacter jejuni and Campylobacter coli, respectively, out of 60 C. jejuni and 18 C. coli strains. Our study demonstrated that motility is inconsistent with biofilm-forming ability, suggesting that motility is not a single factor affecting biofilm formation of Campylobacter . Moreover, there was no clear relationship between antibiotic resistance and biofilm-forming ability. DNase I treatment significantly inhibited the biofilm formation or degraded the mature biofilms of 3 C. coli and 1 C. jejuni biofilm-forming strains ( p  < 0.05). It suggests that extracellular DNA plays a significant role in the biofilm formation of these strains. Collectively, our study demonstrated that biofilm-forming ability is not strongly correlated with motility and antibiotic resistance in Campylobacter and that extracellular DNA is required for biofilm formation of the isolated Campylobacter strains. It also suggests that DNase I is a potential method for the control of Campylobacter biofilms. Highlights: Campylobacter strains were isolated from 37 (30%) of 124 raw chickens. Fourteen (18%) of 78 isolates were able to form biofilm. DNase I treatment significantly reduced Campylobacter biofilms. There was no correlation between biofilm-forming ability and motility. There was no correlation between biofilm-forming ability and antibiotic resistance.